KINERJA KOMITE NASIONAL KESELAMATAN UNTUK INSTALASI LISTRIK DALAM PEMERIKSAAN INSTALASI PEMANFAATAN TENAGA LISTRIK PELANGGAN TEGANGAN RENDAH TAHUN 2010- 2012 DI KOTA PEKANBARU - Yoyok Marwadi; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
In accordance with the law number 30 of 2009 electricity, aimed atsafety for the community that uses the electrical network as well as otherregulations that relate to electrical installation. then formed an independentagency in cooperation with the state electricity company in testing and checkingthe electrical network namely national committee for safety of electricalinstallation. National committee for safety of electrical installation in Pekanbaruestablished in year 2009, it’s existence is considered to extend the bureaucracy incurrent network installation from the State electricity company, still the highpercentage of fires that occurred in Pekanbaru caused by electric konsleting, It isnot considered proper functioning National committe for safety of electricalinstallation the agency serves as the reviewers electrical installation. The theoryused in this research is the theory of performance that there are some aspects thatcan be assessed it’s performance in the context of government as the public sectoraccording to Mahsun namely group of input, group processes, group output,group results, group benefits, the impact group. Determination of performanceindicators to consider following components servicing fee, usage, the quality andstandard of service, service coverage, satisfaction. The methods used in thisresearch is descriptive qualitative. National committee for safety of electricalinstallation in Pekanbaru checks by means of the community submit examinationinstallations that are already installed. National committee for safety of electricalinstallation in Pekanbaru perform inspection in accordance with the Generalrequirements for electrical installation (PUIL 2000) which is the regulation thatestablished the standard for electrical installations, the checks done includeinstallation installation, conductor attached, material, equipment, protectionequipment installation pictures, relationships, the polarity (the color sequence ofthe cable), prisoners of isolation, insulation, ground or ground ardhe.Keywords : Performance, Konsuil, Electric Installation.